(untitled) (Journal of University of Babylon for Engineering Sciences, 2020)
The present study can be split into four aims next its four aims. The first aim was to check the effectiveness of compressive strength of normal concrete on the structural behavior of continuous beams.The second aim was to study the effectiveness of concrete type on the structural behavior continuous beams. The third aim was to study the effectineness of steel fibre ratio from (0 to 2.5%) on the structural behavior of RPC continuous beams. The fourth aim was to study the effectiveness of longitudinal reinforcement bar on the structural behavior of RPC continuous beams by using (CFRP and GFRP). Therefore, nine continuous beams consist of two span were tested under one-point loading for each span. Seven All beams had the matching overall length of 2700 mm, the clear span distance equal to 1250 mm foe each span, and the same width of 150 mm. The test results show that the continuous beam made with RPC had a superior ultimate load compared with the NC continuous beam and that the ultimate load increased when steel fibre ratio increased. The ultimate load of the continuous beam was also Found to be increased when the using of CFRP bar as a longitudinal reinforcement ratio. In supplement, the ultimate load of the continuous beam was decrees when using GFRP bar as a longitudinal reinforcement ratio.